PERBANDINGAN TARIF JASA RAWAT INAP MENGGUNAKAN METODE TRADITIONAL COSTING DAN ACTIVITY BASED COSTING (STUDI KASUS RS JAMBI) - Meliza Putriyanti Zifi; Zainal Arifin Renaldo; Raihania Salsabila (Universitas Pamulang, 2020)
This study aims to find out how to implement the activity based costing method as the basis for determining the rates of inpatient services at Jambi Hospital. In conducting this research, the method used by the writer is quantitative descriptive method. Based on the results of the study, the tariff setting uses the activity based costing method to produce cheaper rates for VIP, Class I, and Class II, while generating more expensive rates for Class III compared to the rates set by Jambi Hospital. Rates for inpatient services with an activity based costing method for VIP Rp 670.435, Class I Rp 431.491, Class II Rp 373.275, and Class III Rp 331.508.